Processing of fecal samples for study of Cryptosporidium sp. by PCR - Pérez-Cordón, Gregorio (2005)
The present paper describes a protocol applied to fecal samples of cattle for the isolation and purification of Cryptosporidium sp. oocysts and the possible use of the same ones for genetic studies by means of PCR.